Distribución espacial y tendencias de indicadores agroclimáticos en la España peninsular - Serrano Notivoli, Roberto; Beguería, Santiago (Geographicalia, 2021)
A new dataset of 12 agroclimatic indicators calculated over a 5x5 km grid in 1981-2010 period is presented for peninsular Spain. The calculation of the indicators was based on the information of maximum and minimum temperatures obtained from the STEAD dataset. Normal values were mapped for all the indicators and the spatial distribution of the temporal changes was described through a trend analysis. Results showed a wide dependence from the geographical factors (elevation, latitude and distance to the coast) in the spatial distribution of the normal values. However, this influence was minimized in the trends to the Mediterranean coast and mountainous areas. A remarkable advance in frost dates was noticed alongside a decrease in the number of the events, with a high spatial variability. Those indicators of thermal sums showed a significant increase as a consequence of the raising temperatures in spring and summer.
Keywords: Agroclimatology; temperature; climatology; trends; Spain